The number of osteoblasts and osteoclasts in bone remodeling of bone defects caused by peri-implantitis using Anadara granosa bone graft: an experimental study - Ariestania, Vivin; Hendrijantini, Nike; Prahasanti, Chiquita; Kurniawan, Hansen; Ashrin, Meinar Nur; Nanik, Chaterina Diyah; Apsari, Anindita; Megantara, Rizko Wira Artha; Sari, Rima Parwati; Hermanto, eddy; Fauzia, Bunga; Matsuyama, Miwa (Universitas Padjadjaran, 2025)
Introduction: Peri-implantitis treatment aims to replace the damaged bone with new and healthy tissue during bone remodeling process. Bone grafts are materials used to stimulate the formation of new bone. Bone graft material derived from Anadara granosa (AG) can be synthesized into hydroxyapatite–tricalcium phosphate (HA-TCP) at a 70:30 ratio, which supports bone regeneration, as indicated by an increase in osteoblast numbers and decrease in osteoclast numbers. This study aims to analyze the effectiveness of Anadara granosa bone graft in the number of osteoblasts and osteoclasts during bone remodeling process. Methods: This study employed an experimental design with a post-test only control group. A total of 84 mice were divided into 12 groups (7 mice per group): negative control (K−), positive control (K+), and treatment group (P), each observed on days 14 and 28. Histological analysis was performed to count osteoblasts and osteoclasts. Data were analyzed using one-way ANOVA. Results: The number of osteoclasts was significantly reduced in the treatment groups (P14: 7.00 ± 1.528; P28: 6.57 ± 1.512) compared to the positive controls (K+14: 13.86 ± 2.410; K+28: 14.29 ± 1.496). On the contrary, the number of osteoblasts increased in the treatment groups (P14: 7.14 ± 1.676; P28: 8.57 ± 1.272) compared to the positive controls (K+14: 2.57 ± 1.512; K+28: 3.86 ± 1.574). Statistical analysis indicated that osteoblasts showed significant differences after AG treatment (p<0.05), and the ANOVA test showed significant differences in osteoclast number after AG treatment (p<0.05). Conclusion: The number of osteoblasts increases while the number of osteoclast reduces in bone remodelling of bone defect caused by peri-implantitis using AG bone graft.